The effect of busy book media on knowledge level dental and oral health in children - Utami, Sri Pandu; Darmawangsa, Darmawangsa; Mahata, Intan Batura Endo; Ashari, Caisar (Jurnal PADE: Pengabdian & Edukasi, 2023)
The World Health Organization (WHO) in World Oral Health Day 2020 states that around 90% of the world's population has experienced dental and oral diseases. Among them 78% occur in children or about 573 million children who experience tooth and mouth decay due to lack of maintaining dental and oral health, children who suffer from tooth decay will cause discomfort that interferes with eating and sleeping patterns, causing children to lose concentration and causing disruption of the daily learning process at school. The purpose of this study was to determine the effect of busy book media on the level of knowledge of dental and oral health in children who came to RSGM Baiturrahmah. This study used an experimental design with a One Group pre-test-post-test design. Samples were taken using the Slovin formula, obtained as many as 30 students. Data were analyzed using the Wicoxon Signed Ranks Test. Based on the results of data analysis carried out, it shows that there is a significant difference with the test results of 0.001 (p <0.05) in the data before and after being given dental and oral health education using the Busy Book Media. Busy Book on children's knowledge level.